Multimodal cell death drives the immunopathogenesis of RSV infection - Yang, Tianxiang; Mi, Zhizhong; Li, Zhaolong (Frontiers in Immunology, 2025)
Respiratory syncytial virus (RSV) is a major cause of severe respiratory tract infections in infants, older adults, and immunocompromised individuals. Despite decades of research, effective therapies are limited, largely due to an incomplete understanding of how infected cells and immune responses interact to shape disease outcomes. Recent evidence indicates that RSV activates multiple regulated cell death (RCD) programs-including apoptosis, necroptosis, pyroptosis, ferroptosis, and autophagy-associated cell death which interact through shared molecular mediators to form a multimodal cell death (MMCD) network. This integrated system regulates the balance between viral clearance and immunopathological injury. Central mediators such as caspase-8, RIPK3, and NLRP3 act as molecular hubs coordinating these death programs and amplifying inflammatory responses. Understanding how MMCD shapes RSV immunopathogenesis provides a unified framework linking cell death to immune dysfunction. This review summarizes recent progress in elucidating the MMCD network, highlights its role in death-inflammation feedback loops, and discusses potential strategies for therapeutic modulation. Conceptualizing RSV disease through the lens of MMCD may guide the development of precision interventions that restore immune homeostasis while preserving antiviral defense.